Мodern methods of diagnosis of endometrial carcinoma - Dimitar Dimitrov; Nadezhda Hinkova; Teodora Semova; Zornitsa Gorcheva; Mirela Vasileva; Elitsa Petkova (Journal of Biomedical & Clinical Research)
The main methods of histological diagnosis of endometrial carcinoma are dilatation and curettage, fractional curettage, and diagnostic hysteroscopy with endometrial biopsy. This retrospective study aims to compare the preoperative histological results obtained by different diagnostic methods with the postoperative ones in patients with endometrial carcinoma and determine the most accurate and safest method for diagnosing the disease. From 06.2020 to 09.2023, a retrospective study was conducted on 80 patients with histologically proven carcinoma of the endometrium, treated at University Hospital Saint Marina-Pleven. The mean age of the patients was 58.04 ± 10.46, ranging from 28 to 78. The comparative analysis of the discrepancies of the histological verification methods in the evaluation of the preoperative and postoperative histological result showed that a statistically significantly higher percentage of discrepancies (19.5%) had the dilatation and curettage compared to the zero discrepancy of the hysteroscopy (0.0%). The relative proportion of discrepancies of the fractional curettage is 14.3%. The cytological result was negative for tumor cells in 97.5% and positive in 2.5%. In all patients with a positive cytological result for tumor cells, the method of histological verification was dilatation and curettage. Performing diagnostic hysteroscopy and observing safety principles such as creating low intrauterine pressure and short operative time is a safe and reliable method for diagnosing endometrial carcinoma.